2018
DOI: 10.1007/s00213-018-5012-7
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal circuits signaling active avoidance retrieval and extinction

Abstract: Objective Neurons in PL and IL project densely to two areas implicated in active avoidance: the basolateral amygdala (BLA) and the ventral striatum (VS). We therefore combined c-Fos immunohistochemistry with retrograde tracers to characterize signaling in platform-mediated active avoidance. Methods Male rats were infused with retrograde tracers (CTB, FB) into basolateral amygdala and ventral striatum and conditioned to avoid tone-signaled footshocks by stepping onto a nearby platform. In a subsequent test se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 49 publications
2
24
0
Order By: Relevance
“…It is unlikely that the effect of anti-BDNF in PL is due to an unintended diffusion into neighboring IL, because infusing the same volume of anti-BDNF into PL or IL had differing effects on extinction of conditioned freezing [14]. Consistent with our PL findings, it was recently reported that pre-training lesions of PL impair extinction of lever-press active avoidance [43], and extinction of avoidance in our task activates PL neurons projecting to ventral striatum (Martínez-Rivera et al, 2018 in press) [44].…”
Section: Discussionsupporting
confidence: 90%
“…It is unlikely that the effect of anti-BDNF in PL is due to an unintended diffusion into neighboring IL, because infusing the same volume of anti-BDNF into PL or IL had differing effects on extinction of conditioned freezing [14]. Consistent with our PL findings, it was recently reported that pre-training lesions of PL impair extinction of lever-press active avoidance [43], and extinction of avoidance in our task activates PL neurons projecting to ventral striatum (Martínez-Rivera et al, 2018 in press) [44].…”
Section: Discussionsupporting
confidence: 90%
“…Active avoidance training increases expression of c-Fos in the shell substructure of the nucleus accumbens (NAcSh) [28], expression of the early growth response protein 1 (Egr1) in the orbitofrontal and dorsal anterior cingulate cortex (CG1), and in the hippocampal CA1 region [29]. It also fosters expression of the activity-regulated cytoskeleton-associated protein (Arc/Arg3.1) in the dentate gyrus (DG) of the hippocampus [29].…”
Section: Adaptive Coping and Functional Neuroplasticitymentioning
confidence: 99%
“…It also fosters expression of the activity-regulated cytoskeleton-associated protein (Arc/Arg3.1) in the dentate gyrus (DG) of the hippocampus [29]. Retrieval of the acquired avoidance enhances expression of Egr1 in the DG and increases c-Fos expression in neurons of the prefrontal cortex (pFC) projecting toward the basolateral amygdala (BLA) and the ventral striatum (VS) [28,29]. Extinction of active avoidance increases c-Fos expression in neurons of the pFC projecting toward the BLA and the VS, as well as brain-derived neurotrophic factor (BDNF) expression in the ventral hippocampus (vHPC) [28,30].…”
Section: Adaptive Coping and Functional Neuroplasticitymentioning
confidence: 99%
See 2 more Smart Citations